Gender aspects of digital ambassadorship: role of employees in employer branding strategies - M. F. Aliev (Цифровая социология)
In the digital age, companies face a myriad of competitive opportunities, especially in attracting and retaining talented employees. In this context, the purpose of this article is to better understand how employees can mobilise to promote a company’s brand in digital social networks and become effective digital ambassadors. To achieve this goal, a theoretical framework has been established based on a literature review on employer branding and the concept of digital ambassadorship. Particular attention is paid to gender aspects of this issue. Gender studies allow to examine the impact of social constructions of gender on perception and behaviour of employees in digital social networks. The article analyses the possibility of influence of stereotypes and inequality on the role of the staff in employer branding strategies through digital ambassadorship. The research offers a discussion of how companies can incorporate the gender aspects into their strategies of branding and employee mobilisation in digital social networks. Opportunities to create an inclusive and diverse environment are considered as well as the development of policies and practices that promote equality and participation of all the personnel in digital ambassadorship. This article aims to explain the gender aspects of the phenomenon in question and the role of the workers in employer branding strategies. It offers practical recommendations and research perspectives for companies seeking to maximise the potential of their employees in digital social networks.